Knowledge of breast cancer and its risk factors among Al-Quds university students in Palestine - Ghrayeb, Farid Abdulwahab; Rimawi, Omar; Nimer, Azzam (International Journal of Research in Medical Sciences, 2018)
Background: Cancer is a major public health problem globally. The incidence of cancer is escalating rapidly in many low- and middle-income countries like Palestine due to the epidemiological transition. This could be due to lack of awareness, knowledge and beliefs about breast cancer and its management among females. Aims and objectives was to determine knowledge of breast cancer risk factors, symptoms and early detection methods among Al-Quds University female students. Methods: A descriptive cross-sectional study conducted over a period of 6 months in Al-Quds University. Study population was 332 female university students. Data was collected by using self-administered questionnaire. Results: The most widely known risk factors by the students were old age 62.7%, followed by obesity 44% and never being pregnant 30.7%. Approximately half of the students (48.8%) identified breast lump as a symptom for breast cancer. However, non lump symptoms were less known and less than half were aware of other warning signs. Only 48.5 % of students identified correctly the appropriate time to perform breast self examination. Conclusions: The findings of this study showed a low level of knowledge on breast cancer risk factors, early warning signs and BSE among female university students. Therefore, effective educational programs are required to improve the knowledge level of university students regarding breast cancer and related practices.